2010
DOI: 10.1021/ma100609k
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in Ordered Polydisperse Polyolefin Diblock Copolymers

Abstract: The morphologies of polydisperse ethylene-octene diblock copolymers, synthesized via a novel coordinative chain transfer polymerization process, are examined using two-dimensional synchrotron small-angle and wide-angle X-ray scattering on flow-aligned specimens. The diblock copolymers comprise one amorphous block with high 1-octene content and one semicrystalline block with relatively low 1-octene content, and each block ideally exhibits the most-probable distribution. Near-symmetric diblocks with a sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 60 publications
5
102
0
Order By: Relevance
“…In OBCs, the hard blocks are long enough to form well‐developed lamellar crystals and space‐filling spherulites can be formed even when the crystallinity is as low as 7% . Many studies of the crystallization, morphology and mechanical properties of OBCs have been conducted . It is found that in OBCs the hard blocks are subjected to the constraint imposed by covalent linkages with non‐crystallizable soft blocks, and crystallization of the hard blocks always occurs simultaneously but in competition with microphase separation .…”
Section: Introductionmentioning
confidence: 99%
“…In OBCs, the hard blocks are long enough to form well‐developed lamellar crystals and space‐filling spherulites can be formed even when the crystallinity is as low as 7% . Many studies of the crystallization, morphology and mechanical properties of OBCs have been conducted . It is found that in OBCs the hard blocks are subjected to the constraint imposed by covalent linkages with non‐crystallizable soft blocks, and crystallization of the hard blocks always occurs simultaneously but in competition with microphase separation .…”
Section: Introductionmentioning
confidence: 99%
“…Even if this analysis can be successfully carried out for a given sample, it is not easily transferrable to other samples because the nature of the paracrystalline distortions cannot be assumed constant. It is preferable to attempt to mitigate sources of paracrystallinity prior to the measurement by, for example, minimizing polydispersity during synthesis or through fractionation and annealing samples in the melt for an extended period …”
Section: Resultsmentioning
confidence: 99%
“…The comonomer incorporation in the hard and soft segments is not clear. There is usually certain amount of random copolymer impurities in the commercial OBC products [18,19]. In researching OBC…”
Section: Introductionmentioning
confidence: 99%